Shifting Authority, Shaping Spirituality: A Qualitative Digital Survey of Religious Practices among the Indonesian Muslim Students - Mohammad Muafi Himam; Ahmad Nadhif Abdul Mujib; Dina Dina; Muhaddibul Irfani (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The digital transformation has reshaped how digital-native university students experience religious life. This study examines how Muslim students in Indonesia engage with, interpret, and negotiate their religious practices in digital spaces. Using a qualitative digital survey design with narrative prompts, data were collected between April 15 and May 1, 2025 through an online narrative-style questionnaire completed by 84 Muslim students from STAI Al-Anwar Sarang Rembang, an Islamic college rooted in the pesantren tradition. Thematic analysis was employed to identify key patterns in spiritual transformation, online community participation, and the dynamics of authority and affect in digital religiosity. Findings indicate that digital media not only facilitates access to Islamic knowledge but also structures new patterns of hybrid worship and emotional engagement. Students demonstrate reflective agency in filtering online religious content and building virtual connections with fellow Muslims across diverse regions, while also facing challenges such as authority confusion, polarized viewpoints, and religious anxiety triggered by online exposure. The study concludes that the digital realm functions as an alternative and complementary arena for religious life among students and underscores the urgent need for critical, inclusive, and context-sensitive religious digital literacy to guide spiritual development in an increasingly mediatized society.